Ethnobotanical inventory and indigenous therapeutic applications of wild medicinal plants in Parishing valley, District Astore, Gilgit-Baltistan, Pakistan - Khadim, Salim; Hyder, Sujjad; Zuhra, Tehseen; Abbas, Hasnain (Ethnobotany Research and Applications, 2024)
Background: This research, through an ethnobotanical survey, explores the diverse array of wild medicinal plants in Parishing Valley, District Astore, Pakistan. The study investigates traditional knowledge continuity, assesses medicinal plant familiarity, and identifies vital regional treatments. Methods: In the field, we collected ethnobotanical data using methods included free listings, key informant interviews, and semi-structured interviews. From seven villages of Parishing Valley, 160 local informants were involved in interviews and questionnaire distribution. To gauge the importance of plant species, we applied indices, Relative Frequency Citation (RFC), Use Value (UV), Fidelity Level (FL), and Informant Consensus Factor Index (ICF). Results: The study revealed the presence of 90 wild medicinal plant species in the region, belonging to 79 genera and 35 families, utilized for treating various ailments among Parishing Valley residents. Asteraceae emerged as the predominant family (13 species). The habit category, herbs were dominated with (72%), shrub with (16%), trees about (8%) and sub-shrub (4%) used in the study area as folk medicine, primarily utilizing leaves (34.4%) in traditional practices. Decoction (63%) was a prominent method for utilizing medicinal plants. The highest RFC reported for Thymus linearis was (0.8), UV for Delphinium brunonianum was (0.95), FL for Thymus linearis was (97.5%) and ICF for the Digestive system (0.91) highlighting their prevalence and significance in the region. Conclusion: In Parishing Valley, the healing traditions of wild plants are vital for healthcare, emphasizing the importance of preserving indigenous knowledge for sustainable resource use. Further research is crucial for uncovering deeper local perspectives. Keywords: Parishing Valley, Astore, Ethnobotany, ethnomedicine, indigenous knowledge, medicinal plants, Relative Frequency Citation